Suriname. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Suriname during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, exports, technology, family farming, innovation, micro-irrigation, resilience against climate change, health and food safety, nutritional security and permaculture, through Perone Hive technology. Likewise, work was done on the production of vegetables, on the management of natural resources and the environment, on the rehabilitation of soils and on access to water, combating contamination caused by mercury and droughts. Finally, the inclusion of women and youth in agricultural processes was supported, in the improvement of the packaging of products, under international standards and in the use of the web as a tool for the improvement of agricultural processes.